Computer Science &Amp; Information Technology (CS &Amp; IT) 2017
DOI: 10.5121/csit.2017.70401
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Detection of Violent Content in Arabic Social Media

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Experiments revealed that combining the seed word list with the extended list generated the best F1 score of 60%. Authors in [4] presented a more detailed dataset for religious hate speech in dialectical Arabic. The dataset comprised 6,600 tweets using religious-related keywords.…”
Section: B Existing Arabic Datasetsmentioning
confidence: 99%
“…Experiments revealed that combining the seed word list with the extended list generated the best F1 score of 60%. Authors in [4] presented a more detailed dataset for religious hate speech in dialectical Arabic. The dataset comprised 6,600 tweets using religious-related keywords.…”
Section: B Existing Arabic Datasetsmentioning
confidence: 99%
“…Abdelfatah et al (2017) [16] proposed a new framework aiming at separating violent and non-violent Arabic tweets over Twitter by using sparse Gaussian process latent variable model (SGPLVM) followed by k-means. Experiment started by collecting 16234 Arabic tweets then pre-processing tweets by removing stop word and web links, after that they annotated manually by at least five different annotators and only tweets have a confidence score more than 0.7 are applied, then two set of experiments have been carried out.…”
Section: Related Workmentioning
confidence: 99%